Alectinib versus crizotinib in ALK‐positive advanced non‐small cell lung cancer and comparison of next‐generation TKIs after crizotinib failure: Real‐world evidence. (26th May 2022) - Wang, Yurong; Shen, Shujing; Hu, Peizhu; Geng, Di; Zheng, Ruipan; Li, Xingya
Abstract: Background: Anaplastic lymphoma kinase (ALK) fusion is a prognostic indicator for patients with non‐small cell lung cancer (NSCLC) receiving tyrosine kinase inhibitors (TKIs). The real‐world data of ALK TKIs remain a major concern. Methods: Patients with ALK‐positive advanced NSCLC, who received crizotinib or alectinib treatment in first line, were retrospectively reviewed. ALK status was detected using immunohistochemistry (IHC) or next‐generation sequencing (NGS). Clinical outcomes have been comprehensively analyzed between TKIs, ALK fusions, EML4‐ALK variants, and next‐generation TKIs after crizotinib failure. Results: One hundred sixty‐eight patients were successively enrolled (crizotinib, n  = 109; alctinib, n  = 59). Alectinib showed consistent superiority in progressive‐free survival (PFS) over crizotinib (hazard ratio [HR]: 0.43, 95% confidential interval [CI]: 0.24–0.77, p  = 0.004). Multivariate Cox regression showed chemotherapy (CT) prior to TKIs or synchronous chemotherapy seemed not to improve PFS compared to ALK inhibitors alone ( p  > 0.05). And, alectinib was superior to crizotinib in prolonging intracranial PFS (HR 0.12, 95% CI: 0.03–0.49, p  = 0.003). Patients in EML4 group had a better prognosis than those in non‐EML4 group after alectinib administration (HR 0.13, 95% CI: 0.03–0.60, p  = 0.009). TP53 co‐mutations were relatively common (34.0%) and associated with adverse outcome in ALK‐positive patients (adjusted HR 2.22, 95% CI: 1.00–4.92, p  = 0.049). After crizotinib failure, 33 patients received a sequential application of next‐generation ALK TKIs. Compared to ceritinib and brigatinib, alectinib might have better PFS ( p  = 0.043). Conclusion: Our results revealed alectinib had better PFS and higher intracranial efficacy compared to crizotinib in ALK‐positive NSCLC, and might improve PFS by comparison with ceritinib and brigatinib after crizotinib failure. Abstract : 1. Chemotherapy prior to TKI or in combination with TKI showed no improvements in PFS compared to ALK inhibitors alone. 2. Alectinib showed better PFS and higher intracranial efficacy by comparison with crizotinib, especially in patients with fusion involving EML4‐ALK. 3. After failure of crizotinib, alectinib might have better PFS compared to ceritinib and brigatinib. 4. TP53 co‐mutations were relatively common and associated with adverse outcome of ALK‐positive NSCLC.